2005
DOI: 10.1088/1742-5468/2005/09/l09001
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries and novel universal properties of turbulent hydrodynamics in a symmetric binary fluid mixture

Abstract: We elucidate the universal properties of the nonequilibrium steady states (NESS) in a driven symmetric binary fluid mixture, an example of active advection, in its miscible phase. We use the symmetries of the equations of motion to establish the appropriate form of the structure functions which characterise the statistical properties of the NESS of a driven symmetric binary fluid mixture. We elucidate the universal properties described by the scaling exponents and the amplitude ratios. Our results suggest that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…We show for the first time that although the exponents associated with b are multiscaling (like the exponents for u), the equal-time exponents for ψ show simple-scaling. Our results are similar to the numerical quasi-Lagrangian (in two-dimensional flows) [13] and in agreement with the predictions of one-loop field theoretical [14] studies of the SBF system.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…We show for the first time that although the exponents associated with b are multiscaling (like the exponents for u), the equal-time exponents for ψ show simple-scaling. Our results are similar to the numerical quasi-Lagrangian (in two-dimensional flows) [13] and in agreement with the predictions of one-loop field theoretical [14] studies of the SBF system.…”
Section: Introductionsupporting
confidence: 89%
“…Our results may be explained from the analytical framework based on symmetry arguments developed in Ref. [14], where it has been shown that the presence of an additional continuous symmetry (kind of a gauge symmetry), not present in the passive scalar turbulence model, is responsible for the simple scaling behaviour of ζ ψ p . It would be interesting to investigate the properties of the turbulent NESS of SBF at low temperature, below the consolute point, when instabilities leading to phase separation competes with turbulent mixing.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations